Cloning, purification and preliminary X-ray data analysis of the human ID2 homodimer - Wong, Marie V. (International Union of Crystallography, 2012)
The ID proteins are named for their role as inhibitors of DNA binding and differentiation. They contain a helix–loop–helix (HLH) domain but lack a basic DNA-binding domain. In complex with basic HLH (bHLH) transcription factors, gene expression is regulated by DNA-binding inactivation. Although the HLH domain is highly conserved and shares a similar topology, the IDs preferentially bind class I bHLH-group members such as E47 (TCF3) but not the class III bHLH member Myc. A structure of an ID protein could potentially shed light on its mechanism. Owing to their short half-lives in vivo and reported in vitro instability, this paper describes the strategies that went into expressing sufficient soluble and stable ID2 to finally obtain diffraction-quality crystals. A 2.1 Å resolution data set was collected from a crystal belonging to space group P3(1)21 with unit-cell parameters a = b = 51.622, c = 111.474 Å, α = β = 90, γ = 120° that was obtained by hanging-drop vapour diffusion in a precipitant solution consisting of 0.1 M MES pH 6.5, 2.0 M potassium acetate. The solvent content was consistent with the presence of one or two molecules in the asymmetric unit.